2019
DOI: 10.1002/pssr.201900376
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Coarsening of Nanoporous Gold Nanowires by In Situ Scanning Transmission Electron Microscopy During Annealing

Abstract: Over the past decades, porous gold has been used in plenty of applications such as catalysis or sensor detection. However, the nanoscale size of both the ligaments and pores makes such material very sensible to temperature. Indeed, the increase in temperature induces coarsening of the structure which can be detrimental for various applications. In this context, understanding of the coarsening on nanoporous gold (NPG) is crucial. In this communication, in situ scanning transmission electron microscopy (STEM) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
(107 reference statements)
1
8
0
Order By: Relevance
“…Recent kinetic Monte Carlo and molecular dynamics simulations also revealed that structures with a low relative density exhibited a surface stress-driven dislocation movement leading to coarsening by ligament collapse 22 . This mechanism was also further supported by observation via in situ transmission electron microscopy in 2D 76 .…”
Section: Resultssupporting
confidence: 57%
“…Recent kinetic Monte Carlo and molecular dynamics simulations also revealed that structures with a low relative density exhibited a surface stress-driven dislocation movement leading to coarsening by ligament collapse 22 . This mechanism was also further supported by observation via in situ transmission electron microscopy in 2D 76 .…”
Section: Resultssupporting
confidence: 57%
“…The majority of thin-film studies on NPG’s morphology evolution have been focused on near room temperature dealloying (i.e., 20–90 °C) at large time scales (i.e., when the residual Ag content is negligible, typically between 0 and 5 at. %), and on annealing post-treatments of dealloyed samples. At large dealloying time scales, pore coarsening is driven by thermally activated surface diffusion to minimize curvature and surface energy of the metastable nanoporous structure . This is the case because Ag is generally assumed to be depleted and to have a minimal effect on the coarsening process. , However, at short dealloying time scales (i.e., when the residual Ag content is greater than 5 at.…”
Section: Resultsmentioning
confidence: 99%
“…The SEM images were collected and analyzed from our measurements and the literature [ 19 , 20 , 21 , 22 , 23 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] with Fiji [ 42 ]. Binary images were obtained by converting solid and voids into 1 and 0 values, and then different procedures were applied to obtain the microstructural information:…”
Section: Methodsmentioning
confidence: 99%